Cruelty, Violence and Education by Michel de Montaigne. An Essay on Pedagogical Deontology - Włodarczyk, Rafał (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2022)
The aim of this paper is to analyse the phenomenon of cruelty according to pedagogical deontology. Cruelty is a significant threat to the educational relationship for two reasons: it is a form of aggression and occurs mostly in a veiled or camouflaged form. The author refers to concepts of cruelty by Michel de Montaigne and Judith N. Shklar and indicates the difference between cruelty and violence and highlights the measures to prevent the emergence of atrocities in education and everyday life.
Keywords: cruelty; aggression; violence; education; pedagogical deontology